Effects of intensive nutrition education and counseling on nutritional status of pregnant women in East Shoa Zone, Ethiopia - Wakwoya, Ermias Bekele; Belachew, Tefera; Girma, Tsinuel (Frontiers in Nutrition, 2023)
Background: Maternal malnutrition is widespread throughout the world, with Sub-Saharan Africa and Asia bearing the brunt of the burden. The aim of this study was to assess the effect of intensive nutrition education and counseling on nutritional status during pregnancy. Methods and Materials: The study was a one-year two-arm parallel design cluster randomized controlled trial conducted in East Shoa zone, Ethiopia from January 1, 2021, to February 30, 2022. A total of 374 were enrolled in the intervention (n = 185) and control (n = 189) groups. End-line data were collected from 163 women, from each intervention and control group. The intervention package provided was a three counseling sessions by trained midwives, a 3 page take-home brochures prepared in local languages distributed and 18 weekly serial short message texts were delivered. The women in the control group received routine nutrition education from the health facilities. After adjusting for potential confounders, a linear mixed-effects model was used to assess the intervention effect. Results: After the intervention, the mean mid-upper arm circumference in the intervention group increased by 36% (23.08 Vs 23.44, p < 0.01). Similarly, the proportion of under nutrition in the intervention group was 11% (25% Vs 36%, p = 0.02) lower compared to the control group. At the end of the trial, women in the intervention group had significantly better nutritional status than women in the control group (β = 0.47, p < 0.01). Conclusion: This study found that intensive nutrition education and counseling using the health belief model was effective in improving nutritional status and reducing under nutrition among pregnant women. As a result, nutrition education and counseling using HBM constructs, as well as regular reminder messages, should be provided to pregnant women as part of the routine antenatal care service. Keywords: Nutrition, Pregnancy, MUAC, RCT, Ethiopia